Assist me or replace me? Uncovering the influence of AI awareness on employees’ counterproductive work behaviors - Bai, Shizhen; Zhang, Xiaoxue; Yu, Dingyao; Yao, Junru (Frontiers in Public Health, 2024)
Objective Drawing on the conservation of resources theory (COR), the research aims to reveal the influence of artificial intelligence (AI) awareness on employees’ mental health and behaviors, particularly examining whether and how employees’ AI awareness impacts their counterproductive work behaviors (CWB) in human-intelligence collaborations. Methods Data was collected from 327 Chinese employees who collaborated with AI in sales, manufacturing, logistics, and other industries. The measurement instruments included scales for AI awareness, psychological contract (PC), emotional exhaustion (EE), and counterproductive work behavior (CWB). We used Hayes’s PROCESS macro to analyze the data. Findings AI awareness had a significant positive impact on CWB (β = 0.448, p < 0.01). PC and EE play a role as partial mediators in the relationship between AI awareness and CWB. The mediating pathways consist of three sequences: “AI awareness → PC → CWB,” “AI awareness → EE → CWB” and “AI awareness → PC → EE → CWB,” with the respective contributions to the overall effect amounting to 8.04, 18.53, and 4.91%. Discussion Our research contributes to the study of AI in the management field by elucidating the relationship between AI awareness and CWB, as well as the mediating mechanisms of this relationship, which enriches the literature on CWB and expands the understanding of the associations between AI and CWB.